The use of scanning electron microscopy and fixation methods to evaluate the interaction of blood with the surfaces of medical devices - Nalezinková, Martina; Loskot, Jan; Myslivcová Fučíková, Alena (Scientific reports, 2024)
Testing the hemocompatibility of medical devices after their interaction with blood entails the need to evaluate the activation of blood elements and the degree of their coagulation and adhesion to the device surface. One possible way to achieve this is to use scanning electron microscopy (SEM). The aim was to develop a novel SEM-based method to assess the thrombogenic potential of medical devices and their adhesiveness to blood cells. As a part of this task, also find a convenient procedure of efficient and non-destructive sample fixation for SEM while reducing the use of highly toxic substances and shortening the fixation time. A polymeric surgical mesh was exposed to blood so that blood elements adhered to its surface. Such prepared samples were then chemically fixed for a subsequent SEM measurement; a number of fixation procedures were tested to find the optimal one. The fixation results were evaluated from SEM images, and the degree of blood elements' adhesion was determined from the images using ImageJ software. The best fixation was achieved with the May-Grünwald solution, which is less toxic than chemicals traditionally used. Moreover, manipulation with highly toxic osmium tetroxide can be avoided in the proposed procedure. A convenient methodology for SEM image analysis has been developed too, enabling to quantitatively evaluate the interaction of blood with the surfaces of various medical devices. Our method replaces the subjective assessment of surface coverage with a better-defined procedure, thus offering more precise and reliable results.
Keywords: oxid osmičelý; Histological Techniques; histologické techniky; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; Osmium Tetroxide